Influence of Ag addition on the thermal behavior of the Cu-11 mass% Al alloy - Silva, R. A. G.; Adorno, A. T. [UNESP]; Roque, J. O. [UNESP] (Springer, 2009)
In this work the influence of Ag additions on the thermal behavior of the Cu-11 mass% Al alloy was studied using differential scanning calorimetry, in situ X-ray diffractometry and scanning electron microscopy. The results indicated that changes in the heating rate shift the peak attributed to alpha phase formation to higher temperatures, evidencing the diffusive character of this reaction. The activation energy value for the alpha phase formation reaction, obtained from a non-isotherm kinetic model, is close to that corresponding to Cu atoms self diffusion, thus confirming that this reaction is dominated by Cu atoms diffusion through the martensite matrix.
Keywords: Thermal behavior; Cu-Al alloys; Ag addition